Paint saves the day - Samu, Lucianna (Upper Saddle River, NJ Creative Homeowner, 2009)
Describes how paint can be used as a design element on walls, floors, and furniture items with projects that present techniques and offer instructions on applying each technique in a particular room.
Keywords: House painting; Color in interior decoration -- Handbooks, manuals etc; Interior decoration -- Handbooks, manuals etc